La dimensione individuale e comunitaria della borgata prima della massificazione sociale. Intellettuali e fotografi fra il 1945 e il 1960 - Mancini, Elisabetta (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
This essay investigates the visual and textual representations of the Roman slums (borgate) in Italian illustrated magazines between 1945-1960. Within this time frame, two distinct photographic attitudes emerge. Up until 1952, representations were generally more detached; after 1954, an engaging approach began to develop. Three examples are analysed in detail: a 1946 report by poet Giorgio Caproni, a 1951 article by Libero Bigiaretti (with photographs by Aldo Razzi), and a group of photographs taken by Tazio Secchiaroli in 1952.